Pengaruh Perencanaan Sdm, Manajemen Talenta, Dan Manajemen Pengetahuan Terhadap Kinerja Perawat Pada RS Tk. III. Reksodiwiryo Padang - Hasyya Acika Zulfira; Lasti Yossi Hastini (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to determine the Effect of Human Resource Planning, Talent Management, and Knowledge Management on Nurse Performance at RS TK.III.Reksodiwiryo Padang. The population in this study were all nurses at RS TK.III.Reksodiwiryo Padang totaling 201 people. The sample in this study was 127 people. This study is a quantitative study. The instrument used in this study was a questionnaire. The results of the study using multiple linear regression analysis showed that simultaneously there was an influence of HR planning, talent management, and knowledge management on employee performance and partially HR planning had a positive effect on employee performance, partially talent management had a positive effect on employee performance and partially knowledge management had a positive effect on employee performance.